Whose city is visible? linguistic inequality and spatial belonging in the multilingual landscapes of Indonesian metropolitan peripheries - Zohaib Hassan Sain; Ridhatullah Assya’bani (Indonesian Journal of Language, Space, and Visual Arts, 2026)
Background: Metropolitan peripheries concentrate industrial expansion, commuter mobility, administrative growth, and local identity, yet their multilingual public spaces remain unevenly recognised. Objective: This study examines how linguistic visibility, sign-producing authority, and spatial belonging are organised across Kabupaten Bekasi, Kabupaten Sidoarjo, and Kabupaten Bandung. Method: Using a multi-sited linguistic-landscape design, this study analyses 371 coded signs through a Stratified Linguistic Visibility Matrix, a Sign-Authority and Access Grid, and a Spatial Belonging and Place-Making Protocol. Results: Indonesian dominated governmental and transport domains, while English gained prominence in industrial and commercial settings. Local languages appeared most functionally in heritage, neighbourhood, and selected civic or commercial spaces, with Sundanese receiving broader cross-domain visibility in Kabupaten Bandung than local-language resources in Bekasi and Sidoarjo. Sign authorship further differentiated visibility: governmental and corporate actors controlled durable and consequential signage, whereas community-produced local-language displays were more frequently temporary or spatially restricted. Implication: This study’s implication lies in conceptualising linguistic inequality as unequal access to consequential spatial visibility rather than unequal frequency alone. Novelty: By integrating language salience, institutional authority, sign permanence, domain, and semiotic constructions of belonging, this study offers a relational framework for explaining how metropolitan peripheries recognise some linguistic communities while confining others to symbolic cultural presence within changing urban landscapes